Non‐invasive prenatal diagnosis of achondroplasia and thanatophoric dysplasia: next‐generation sequencing allows for a safer, more accurate, and comprehensive approach. (26th May 2015) - Chitty, Lyn S.; Mason, Sarah; Barrett, Angela N.; McKay, Fiona; Lench, Nicholas; Daley, Rebecca; Jenkins, Lucy A.
Abstract Objective Accurate prenatal diagnosis of genetic conditions can be challenging and usually requires invasive testing. Here, we demonstrate the potential of next‐generation sequencing (NGS) for the analysis of cell‐free DNA in maternal blood to transform prenatal diagnosis of monogenic disorders. Methods Analysis of cell‐free DNA using a PCR and restriction enzyme digest (PCR–RED) was compared with a novel NGS assay in pregnancies at risk of achondroplasia and thanatophoric dysplasia. Results PCR–RED was performed in 72 cases and was correct in 88.6%, inconclusive in 7% with one false negative. NGS was performed in 47 cases and was accurate in 96.2% with no inconclusives. Both approaches were used in 27 cases, with NGS giving the correct result in the two cases inconclusive with PCR–RED. Conclusion NGS provides an accurate, flexible approach to non‐invasive prenatal diagnosis of de novo and paternally inherited mutations. It is more sensitive than PCR–RED and is ideal when screening a gene with multiple potential pathogenic mutations. These findings highlight the value of NGS in the development of non‐invasive prenatal diagnosis for other monogenic disorders. © 2015 John Wiley & Sons, Ltd.